Overview of Language Diversty in the Teaching-Learning Process on Students of Local Language and Literature Education Study program, Universitas Negeri Makassar : Sociolinguistic Studies - Rahim, Ilma; Amir, Johar; Munirah, Munirah (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
This qualitative research aims to describe (1) the form of language variety, (2) factors, and (3) the contribution of Indonesian language variety in learning based on the perspective of Holmes' (2013) language variety analysis. The data of this research are in the form of speech in the form of words and sentences. Source of research data for Makassar language and literature education students' batch 2020 at UNM. The results showed that the variety of languages in the teaching and learning process of PBSD class of 2020 UNM students had four forms: (1) formal language variety; (2) a variety of consultative languages; (3) casual language variety; and (4) variety of familiar languages. The consultative language variety adheres to code-mixing elements, phonological errors, and dialectal elements. This study shows that there are socio-cultural factors, situations, demographics, speech media, and gender. By using supporting teaching materials and language skills, support the Indonesian language.